2005
DOI: 10.1088/0741-3335/47/5a/009
|View full text |Cite
|
Sign up to set email alerts
|

Physics of wire array Z-pinch implosions: experiments at Imperial College

Abstract: A review of recent experiments on the MAGPIE generator (1 MA, 250 ns) aimed at studying the implosion dynamics of wire array Z-pinches is presented. The first phase of implosion is dominated by the gradual ablation of stationary wire cores and gradual redistribution of the array mass by the precursor plasma flow. It is found that the rate of wire ablation depends on the magnitude of the global (collective) magnetic field of the array, and increases with the field. The existence of the modulation of the ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 46 publications
(64 reference statements)
5
64
0
Order By: Relevance
“…This can be interpreted as evidence that significant mass (∼50%) trails the leading implosion front due to magnetic Rayleigh-Taylor-type instability. A qualitatively similar conclusion has been reached for cylindrical wire arrays at 1-20 MA [50,51,40], where it was concluded that 30-50% of the mass may trail behind the fastest implosion front at the foot of the power pulse.…”
Section: Chapter 3 Discussion Of Experimental Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This can be interpreted as evidence that significant mass (∼50%) trails the leading implosion front due to magnetic Rayleigh-Taylor-type instability. A qualitatively similar conclusion has been reached for cylindrical wire arrays at 1-20 MA [50,51,40], where it was concluded that 30-50% of the mass may trail behind the fastest implosion front at the foot of the power pulse.…”
Section: Chapter 3 Discussion Of Experimental Resultssupporting
confidence: 69%
“…This decision was made in order to facilitate assembly of the loads, but also because prior work with cylindrical wire arrays has indicated that too small an inter-wire gap can be detrimental to x-ray power performance [19,22]. The mechanism for degradation has been speculated to be due to an unfavorable modification of the ablated plasma pre-fill profile as wire number is changed [23] or a merging of the current-carrying coronal plasma surrounding the wires early in time, allowing current to jump between adjacent wires and compromising the uniformity of the current path [24]. It is not clear that either of these mechanisms would be relevant to planar wire arrays, which already have a significant initial mass distribution interior to the load, and in which the current distribution between the wires is likely inductive with stronger current density on the outer edges of the array.…”
Section: Return Current Cagementioning
confidence: 99%
“…Evidence for trailing mass extending to the initial outer wire position of a planar wire array at the time of peak x-ray power is shown in Fig. 3.3. A similar conclusion has been reached for cylindrical wire arrays at 1-20 MA [39,40,41], where it was concluded that 30-50% of the mass may trail behind the fastest implosion front at the foot of the power pulse. The fraction of mass left behind the implosion may be exacerbated in planar wire arrays, however.…”
Section: Planar Wire Array Implosion Dynamicssupporting
confidence: 65%
“…3 Recently, by using a novel preconditioned wire array Z-pinch, each individual wire from an aluminum wire array was heated to a vapor state instead of the core-corona structure, and then the ablation phase of the wire array was suppressed and the implosion involved all mass of the array, limiting the level of mass trailing behind implosion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of wire arrays with large wire numbers allows obtaining high radiation power and short X-ray pulses, but one of the limiting factors in the further enhancements is the presence of the axial modulation of the ablation rate of the wires in the array. 3 Recently, the concept of the preconditioned Z-pinch was proposed in which the ablation phase was suppressed and the implosion involved all mass of the array. This was achieved by employing a specially designed two stage wire array (a normal wire array on the top with an exploding wire array in the bottom).…”
mentioning
confidence: 99%